Legitimate military target or victims of crime? - Ivica Šarac (Hum, 2020)
Were the Franciscans from Široki Brijeg killed in February 1945 while participating in the battle or the war crime was committed over them? Although at first such question seems as an inadmissibly simplified doubt, in this case there are only two possibilities indeed: were they murdered as actors in the armed conflicts or killed innocent? On the basis of available archive documents, relevant literature and witness statements the paper seeks to verify the validity of claims on (un)involvement of Franciscans in the armed conflicts in široki Brijeg from 6th to 8th February 1945.